Usulan Model Pengembangan Pariwisata Pantai di Kaki Jembatan Suramadu - Utami, Issa Dyah (Universitas Trunojoyo Madura, 2009)
Suramadu bridge that connect between Java Island with Madura Island will open opportunity for Regency ofBangkalan becomes industrial location of region tourism at East Java: Rongkang beach was one of tourism region at Bangkalan that its positzon close to Suramadu Bridge. At thzs time tourism area at Rongktlng Beach stills wasn't maximal. To it in observational it was made by model optimal utmost of many_ industrial park management alternatives Rongkang's Beaches with dynamic system approaching. This research proposes two area developmental scenarios Rongkang's Beach tourzsm. Devefopmental scenario I of the Beach tourism area Rongkang by nature bY utilizes and pet beach region authenticity and its vicinity. Scenario II. tourism area Development Rongkang' s Beach by undertaking deve1opment in many region, which is by building umpteen interesting modefor tourism.The result of thzs research was pomt out that scenario II are the best. areas developmental modelling ofRongkang's Beach tourism more reasonable and more advantaKes to be compared with Its I. Scenario I inaicate that the cashflow is Rp. 28. 397. 088. 000,- wzth payback period 0,352149 years. Meanwhile cashflow of scenario zs Rp. 667. 942.1.000,- with payoack period 0,149713 years.Key word: Tourism, dynamic system, investment